Living Into One’s Death: Reclaiming Christian Identity and Agency When Facing a Life-Threatening Illness - Waters, Sonia (Pastoral psychology, 2022)
Individuals with a life-threatening illness need space to talk about death, but they also need guides to help them form a meaningful life until they die. Since the medical narrative seeks to fix broken bodies, there is no cultural place for those who are unhealed but not yet dead. Focusing on the Christian faith, the author reviews holistic healing prayer, vocational commitment, and the ars moriendi (art of dying) tradition as resources for retaining identity and agency in this slower kind of death.